Efektivitas Strategi Ta’bir Mushawwar dalam Pembelajaran Bahasa Arab di Madrasah Ibtidaiyah - Mahmudah, Nuur; Khairunnisa (FAKULTAS AGAMA ISLAM UNIVERSITAS BILLFATH, 2024)
Speaking proficiency is one of the main skills in Arabic language learning, but fourth grade students of MI TPI Keramat face difficulties in assembling mufradat and practicing active conversation, mainly due to the lack of varied learning strategies. This study aims to analyze the effectiveness of the ta'bir mushawwar strategy, which uses picture as a media to facilitate students in constructing sentences and telling stories, in improving Arabic speaking skills. With a quantitative approach and pre-experiment design, this study involved 18 students of class IV-C. Data were collected through tests, observations, and interviews, then analyzed descriptively and N-Gain test. The posttest average was 83.06 (very good category) with 88.9% completeness, and the N-Gain score was 0.6398 which showed effectiveness in the medium category. The ta'bir mushawwar strategy offers a solution in the form of a visual and hands-on learning approach that can significantly improve students' speaking skills and make learning more interesting and interactive.